Working With Academic Literacies Case Studies Towards Transformative Practice - Lillis, Theresa; Harrington, Kathy; Lea, Mary; Mitchell, Sally (Open textbook library., 2015)
The editors and contributors to this collection explore what it means to adopt an "academic literacies" approach in policy and pedagogy. Transformative practice is illustrated through case studies and critical commentaries from teacher-researchers working in a range of higher education contexts—from undergraduate to postgraduate levels, across disciplines, and spanning geopolitical regions including Australia, Brazil, Canada, Cataluña, Finland, France, Ireland, Portugal, South Africa, the United Kingdom, and the United States. Key questions addressed include: How can a wider range of semiotic resources and technologies fruitfully serve academic meaning and knowledge making? What kinds of writing spaces do we need and how can these be facilitated? How can theory and practice from "Academic Literacies" be used to open up debate about writing pedagogy at institutional and policy levels?